GC-C-IRMS CHARACTERIZATION OF SYNTHETIC BIS(METHYL-THIO)METHANE IN TRUFFLE FLAVORINGS - BONONI, M.; TATEO, F.; BENEVELLI, F.; PENNETTA, A.; DE BENEDETTO, G. (Italian Journal of Food Science, 2018)
Bis(methyl-thio)methane (BMTM), the molecule which provides “white truffle-like” flavor was characterized by physico-chemical methods. Analysis by GC-C-IRMS of eight samples of synthetic BMTM from various raw material suppliers allowed the investigation of the 13C values. More, ten samples purchased on the Italian flavoring market, declared as synthetic BMTM principal component diluted in olive oil were analyzed by GC-C-IRMS. The results of both sample groups allowed us to define the range of 13C values of synthetic BMTM. We verified if the simple proposed extraction method allows to measure the 13C value of BMTM also identified in seasonings of the Italian market declared on label as “white truffle flavored olive oil”. In all twenty samples purchased on the market, the data strictly corresponded with synthetic BMTM as the principal component. Measurements by 1H NMR made on synthetic BMTM and BMTM extracted from “white truffle-like flavor” confirmed that the adopted extraction method using methanol-d4 determined the isotopic distribution of 13C/12C ratio in two characteristic sites of this molecule.